Development of occupational well-being measurement model in the employee of Abadan University of Medical Sciences - Elham Ehsani Farid; Azin Jaafari; Zarrin Zarrinabadi; Nasrolah Erfani (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Given the importance of healthcare centers and the employees of medical centers and affiliated institutions in providing comprehensive health services to the community, especially patients, as well as training the students in health-related fields, it is crucial to address the occupational well-being of university employees who are prone to physical and mental disorders. Therefore, this study aims to develop a model for the occupational well-being of employees at the Abadan University of Medical Sciences. MATERIALS AND METHODS: Two hundred Abadan University of Medical Sciences employees were selected using stratified sampling. All the selected participants responded to the Demo and Paschoal Well-being at Work Scale (2016). The model parameters were estimated using partial least squares regression based on the collected data. Afterward, the measurement model of occupational well-being was tested using fit indices. Moreover, data analysis was performed using Smart-PLS software. RESULT: The primary results showed that based on the positive correlation indices and t-test results for the factors of occupational well-being, the Demo and Paschoal measurement model had an acceptable fit; moreover, significant internal correlations were observed among the questionnaire items. The composite reliability and Cronbach's alpha coefficients of the factors indicated a high reliability of the occupational well-being measurement model. CONCLUSION: The measurement model of occupational well-being was examined, and it is recommended that future researchers employ the current questionnaire to assess occupational well-being.